Neighborhood-level socioeconomic and urban land use risk factors of canine leptospirosis: 94 cases (2002–2009) - Raghavan, Ram K.; Brenner, Karen M.; Higgins, James J.; Hutchinson, J. M. Shawn; Harkin, Kenneth R. (My University, 2012)
Associations of housing, population, and agriculture census variables, and presence near public places were retrospectively evaluated as potential risk factors for canine leptospirosis using Geographic Information Systems (GIS). The sample population included 94 dogs positive for leptospirosis based on a positive polymerase chain reaction test for leptospires on urine, isolation of leptospires on urine culture, a single reciprocal serum titer of 12,800 or greater, or a four-fold rise in reciprocal serum titers over a 2–4 week period; and 185 dogs negative for leptospirosis based on a negative polymerase chain reaction test and reciprocal serum titers less than 400. Multivariable logistic regressions revealed different risk factors among different census units; however, houses lacking complete plumbing facilities [OR = 2.80, 95% C.I. = 1.82, 4.32 (census unit, block group); OR = 1.36, 95% C.I. = 1.28, 1.45 (census tract); OR = 3.02, 95% C.I. = 2.60, 3.52 (county)]; and poverty status by age (18–64) [OR = 2.04, 95% C.I. = 1.74, 2.39 (block group); OR = 1.53, 95% C.I. = 1.41, 1.67 (census tract); and OR = 1.62, 95% C.I. = 1.50, 1.76 (county)] were consistent risk factors for all census units. Living within 2500 m of a university/college and parks/forests were also significantly associated with leptospirosis status in dogs. Dogs that live under these circumstances are at higher risk for leptospirosis and pet owners should consider vaccination.
Keywords: Leptospirosis; Canine; Socio-economic status; Modifiable Areal Unit Problem (MAUP); Geographic Information Systems (GIS)